Normative Diagrams as a Tool for Representing Legal Systems - Diogo Sasdelli; Alexandre Travessoni Gomes Trivisonno (The Review of Socionetwork Strategies, 2023)
The paper at hand introduces and discusses a diagrammatic method to represent legal norms~first developed by the second author. It is shown how this method can be used to represent not only norms and argument forms originating from classic legal methodology (legal subsumption, analogy, appeal to the contrary), but also more complex legal-theoretical phenomena, especially legal antinomies. Beyond its didactic virtues, the diagram is a useful theoretical tool for investigating how norms interact with each other and how singular actions can be considered as satisfying or violating a given norm.
Keywords: 300; Normative diagrams; Formal representation of norms; Legal antinomies; Legal methodology